Inquiring the generative capacity of urban abstraction and mapping for first-semester basic design studio - Derya Yorgancıoğlu; Doğa Dinemis Aman; Beyza Şat (IDA: International Design and Art Journal, 2023)
The development of students’ critical and creative thinking skills is at the core of the first-semester basic design studio. Students’ perceptual experiences of their environment form the key references of abstraction in this beginning phase. This paper inquires studio approach based on abstraction and mapping as tools for intertwining visual reasoning and bodily experiences in the design process. Focusing on the case study of a basic design studio assignment, the authors analyze the structure, application, and products of the “Urban Abstraction and Mapping” project. The study adopted the case-study method as part of qualitative research approach and dwelled on researchers’ first-hand interaction with a phenomenon within its real-life context, ARCH/MIM101 studios. The findings showed that abstraction and mapping strategies based on students’ bodily experiences in urban contexts raised awareness of design as a generative and iterative research process. Students who were able to reveal and reconstruct the relationship between different forms of knowledge through experiential and conceptual levels of the design process managed to develop heuristic 2D and 3D design strategies. The findings of this study provide a ground for discussions on the effectiveness of teaching/learning methods applied in the introductory level of design education.